The beginning of nature conservation history concerning the designation of protected areas - Centeri, Csaba; Gyulai, Ferenc (JOURNAL OF LANDSCAPE ECOLOGY, 2006)
Designation of the areas for the purpose of nature conservation started a few thousands years ago. The official start of the history of nature conservation was the 19th century. In 1872 Yellowstone National Park was established, this is the official starting date of nature conservation. The newest categories of the IUCN for the management of protected areas were accepted in 1994. We wish to give an overview about the antecedents, about the history of the designation and forming of protected areas, introducing the first protected areas until the First World War.
Keywords: nature conservation; history; world; protected areas